Water and nitrogen use efficiency of common ragweed (Ambrosia artemisiifolia L.) at different nitrogen and water levels - Robert LESKOVŠEK; Klemen ELER; Franc BATIČ; Andrej SIMONČIČ (Acta Agriculturae Slovenica)
Common ragweed (Ambrosia artemisiifolia L.) spread across Europe and other regions is becoming a serious health and economic threat. A pot experiment was conducted in 2011 to determine effect of various nitrogen (N) (10, 100 kg/ha) and water supply regime on resource use efficiency of ragweed. Ragweed plants increased their dry matter production with increased water and N availability. Nitrogen use efficiency (NUE) was decreased with N addition and was not influenced by water availability. Mean nitrogen residence time (MRT) was longer at low N and water levels. In contrast, nitrogen productivity (NP), NUE and water use efficiency (WUE) were all increased with enhanced water supply. A trade-off between parameters of NUE was attributed to differential response of NP and MRT to soil fertility and water supply. Our results confirmed that ragweed displayed high adaptation to unproductive sites. However, ragweed’s greater plasticity in response to water availability compared to N availability suggest, that water supply plays important role in its invasion success and in combination with disturbance ragweed might further spread into more productive environments.